PERANAN GURU PENDIDIKAN AGAMA ISLAM DALAM KETERAMPILAN KOMUNIKASI DAN MEMBANGUN KARAKTER SISWA ERA DIGITAL DI MTS MUSLIMAT NU PALANGKA RAYA - Santiani, Santiani; Sudrajat, Adisti Aulia (Faidatuna, 2024)
Abstract. In an increasingly modern and rapidly advancing era, namely where the advancement of digital era technology and knowledge, especially in the world of education, the role of teachers is very important to prepare a good generation, namely having a character in accordance with religious teachings and state norms and having communication skills. So the role of teachers is very important, especially religious teachers or Islamic religious education teachers. The purpose of this study was made where the progress of the digital era but there are still many shortcomings of students in having a character that is in accordance with religious and state law and there are still many shortcomings in communicating so that because character and communication are very important, especially in today's era and for the future, it is necessary to build student character and communication skills of students in this digital era, so in this study Islamic religious education teachers are taken or become roles in building character and communication skills of students in this digital era. As for the research method using a descriptive qualitative research method which takes data through observation, interviews, and documentation and also takes other literature that supports this research in order to become relevant research that is formed in the form of descriptive qualitative.